A Decentralized and Sustainable Solution to the Problems of Dumping Menstrual Waste into Landfills and Related Health Hazards in India - Bhor, Gautami; Ponkshe, Sayali (European Journal of Sustainable Development, 2018)
In a nation like India which consists of 655 million women, 48% of them are not aware of the proper usage of a sanitary napkin. Disposal of used sanitary pads is a major challenge across India. This study investigates how women manage menstrual waste and the amount of sanitary waste that ends up into landfill. Lack of awareness and immense taboo around menstruation in India adds up to the issues of proper sanitary waste management. This infectious waste, if not handled properly, would pose an immense threat to the oceans, land, and human health. So far while importance was given only to promoting the usage of sanitary napkins, it is equally important that the problems caused by dumping sanitary waste in landfills be addressed. Considering the various hazards caused by this widely accepted yet problematic disposal method, it is necessary to come up with a solution that is sustainable on every front. To avoid proliferation of the problem, a decentralized solution to handle the menstrual waste at its generation point is vital. With this study, we try to conclude best practices to be observed and put forth a solution that is more economical, viable and rational than landfill dumping. Keywords: Menstrual waste, Landfills, Land and water pollution, Health of waste pickers, Decentralized solution